1997
DOI: 10.1007/s005850050434
|View full text |Cite
|
Sign up to set email alerts
|

On storm weakening during substorm expansion phase

Abstract: Abstract. Iyemori and Rao recently presented evidence that the strength of a magnetic storm, as measured by -Dst, weakens, or its rate of growth slows, during the substorm expansion phase. Yet the expansion phase is known to inject energetic particles into the ring current, which should strengthen the storm. We propose to reconcile these apparently contradictory results by combining the virial theorem and a principle of energy partitioning between energy storage elements in a system with dissipation. As applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 10 publications
5
25
0
Order By: Relevance
“…The observed variations of SYM-H may imply that SYM-H (or Dst) is also effected by other magnetospheric currents beside the ring current. It has been suggested that the increase in SYM-H (or Dst) after substorm onsets is related to a reduction in the cross-tail current [Iyemori and Rao, 1996;Siscoe and Petschek, 1997].…”
Section: Observationsmentioning
confidence: 99%
“…The observed variations of SYM-H may imply that SYM-H (or Dst) is also effected by other magnetospheric currents beside the ring current. It has been suggested that the increase in SYM-H (or Dst) after substorm onsets is related to a reduction in the cross-tail current [Iyemori and Rao, 1996;Siscoe and Petschek, 1997].…”
Section: Observationsmentioning
confidence: 99%
“…The result of Iyemori and Rao [1996] therefore appears to be counterintuitive. Siscoe and Petschek [1997] sought to reconcile this apparent discrepancy in terms of the virial theorem, which predicts that Dst actually decreases if less than half of the tail magnetic energy is transferred to the ring current, with the rest of energy dissipated in the ionosphere. Thus the reduction of the tail current (i.e., tail current disruption) at storm time should be crucial for under-standing the result of Iyemori and Rao [1996] and, more generally, the physical meaning of the Dst index.…”
Section: Tail Current Contribution To Dst Indexmentioning
confidence: 99%
“…Recent modeling studies have found that the contribution of the tail current to Dst can be as much as 20% [Friedrich et al, 1999;Turner et al, 2000]. It is possible that the reduction of the tail current intensity, tail current disruption, at substorm onset causes a recovery of Dst, and the associated redistribution of the magnetic energy may explain the result of Iyemori and Rao [1996], as suggested by Siscoe and Petschek [ 1997].…”
Section: Introductionmentioning
confidence: 99%
“…During its course, auroral arcs intensify, move poleward and break up into smaller formations (Akasofu 1976). Substorms are ubiquitous at all solar phases and appear within all types of magnetospheric responses to solar wind input: Embedded within large storms they influence storm development (Daglis et al 2000) and geo-effectiveness (Siscoe and Petschek 1997). They bind the beginning and end phases of magnetospheric convection bays (Sergeev et al 1996a) and are closely related to pseudo-breakups (Aikio et al 1999).…”
Section: Introductionmentioning
confidence: 99%